Chinese Strategic Decision-making on CSR - Wang, Shuo (Springer, 2015)
This research study attempts to provide a comprehensive CSR literature review, analyze corporate social responsibility (CSR) issues from the strategic decision-making (SDM) perspective, and investigate the process of managers’ CSR- related SDM in China. In particular, it utilizes content analysis to examine selected CSR articles from published studies, in order to evaluate the trends in CSR theory development as well as to identify the variables, constructs, and relationships within CSR theory.